COUNSELING ABOUT CHOLESTEROL - UNEPUTTY, MERLIN MONIKA (KAMI MENGABDI, 2025)
Cholesterol is a type of fat produced in the liver and saturated fats in food. Cholesterol is one of the components that make up fat. In fat, there are various components such as triglycerides, phospholipids, free fatty acids, and cholesterol. High cholesterol levels can be caused by dietary factors. The dietary factors that influence cholesterol levels include total fat, saturated fat, and total energy intake. This health education method involves direct participation from the community at Puskesmas Sunter Agung 1, North Jakarta. This activity was conducted by members of groups 5 and6 from the Pharmacist class B 2024, class of 51, on October 17, 2024. Data shows that the average post-test score of correct answers was 89.616%, while incorrect answers were 10.366%. Therefore, it can be concluded that this health education successfully improved the understanding of the community at Puskesmas Sunter Agung 1, North Jakarta.Keyword : Cholesterol, Counseling, Pukesmas.